Pembangunan Sistem DataLab BPS untuk Pengolahan Data Mikro - Almahenzar, Bagus; Anang, Yunarso (Seminar Nasional Official Statistics, 2023)
Data from censuses and surveys conducted by the Central Statistics Agency are urgently needed in various fields, one of which is in projects carried out by government agencies or researchers. The purpose of this research is to build a system that is used in microdata processing. This system provides microdata access to data users but users do not get these microdata files which can be taken home and cannot be accessed at any time through the user's device. Users can only do processing and get output from microdata processing. At the implementation stage, two applications were produced in the BPS DataLab system, namely applicationswebsite and desktop applications. Applicationwebsite used for account requests and requestsproject. Desktop applications are used to limit the user's time in processing data, triggers to start screen recording and restart the computer, and upload files resulting from data processing. Based on the research results, it can be concluded that the BPS DataLab system has fulfilled the research objectives